Reproductive Biology of Pterocaesio tile (Cuvier, 1830) in Supporting Responsible Fisheries Encircling Gillnet - M. Aprillia, Reskyta; Tupamahu, Agustinus; Tuapetel, Friesland; Haruna, Haruna (Agrikan Jurnal Agribisnis Perikanan, 2023)
Pterocaesio tile are generally caught by encircling gill nets using the schooling behavior of these species. The purpose of this study was analyze the biological reproduction of P. tile which induced sex ratio, gonadal maturity level, gonadal maturity index and size at first maturity. Data collection was carried out from October to December 2022. The data collection method was conducted using experimental fishing methods by operating unit gill net with mesh size of 1,75 and 2,0 inch. Fish samples of each actual fishing were measured total length and weight, dissected to determine sex, measured gonad weight and determined the level of gonadal maturity. The results showed that the sex ratio of male fish was higher than female fish. The GML phase is in phases I-V where the immature gonads are more dominant than the mature gonads, the GSI increases as GML increases. The size at first maturity for males is 20.6 cm and 18.6 cm for females.